Educação de jovens e adultos: uma retomada à cidadania - Biffi, Patrícia Cecy (2017)
The objective of this work is to present and analyze the modality of Youth and Adult Education, within a historical perspective of this educational movement in Brazil. Demonstrate the importance of this education for the personal change that this teaching can bring to the interviewed students, young people and adults, who attend this modality in two schools in São Paulo. To verify if the education of young people and adults has influence for the "construction" of the citizenship of the students that attend the school, locus of research for this work.